A crack-free high-strength wear-resistant tungsten-based metal coating with in-situ construction of FCC ductile phase and a preparation method thereof
Patent Information
- Application Number
- CN202611349256.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-02
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]本发明针对现有钨基金属涂层在激光熔覆过程中易开裂的问题,提供一种枝晶间原位生成γ-(Fe,Ni)韧性相的无裂纹高强耐磨钨基金属涂层及其制备方法
[0021](1)本发明转变传统抑制基体稀释的思路,创新性地利用铁基基体熔入熔池的Fe元素与预置W-Ni粉末中的Ni元素发生原位冶金反应。熔入的Fe元素与粉末中的Ni在快速凝固过程中发生协同作用,在脆性W固溶体枝晶间原位构筑热力学稳定的面心立方γ-(Fe,Ni)韧性相;创新性地利用γ-(Fe,Ni)相塑性变形容纳能力与位错储存能力释放热应力集中,有效地松弛凝固冷却过程中的残余拉应力,阻断微裂纹的萌生与扩展。从源头上抑制了裂纹的萌生与扩展,制备出宏观与微观均无裂纹缺陷的高性能钨基金属涂层。
Smart Images

Figure CN123005378A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of metal surface engineering and laser additive manufacturing technology, specifically relating to a crack-free, high-strength, wear-resistant tungsten-based metal coating prepared by laser cladding technology and its preparation method. Background Technology
[0002] Tungsten possesses an ultra-high melting point, high atomic number, high density, and excellent high-temperature strength, wear resistance, and corrosion resistance, making it a promising high-temperature resistant, wear-resistant, and nuclear radiation shielding material with broad application prospects in extreme service environments such as nuclear power plant structural components and high-temperature wear-resistant parts. Currently, wear-resistant and corrosion-resistant components are mainly made of traditional engineering steel or cemented carbide, but under complex stress and service environments such as high temperature, heavy load, and severe wear, the service life of traditional materials is still significantly limited. To meet more stringent operating conditions, the development of tungsten-based materials with higher hardness and wear resistance has become a research hotspot.
[0003] Currently, tungsten-based materials are mainly used in bulk form. However, limitations in technology, material costs, and processing fees restrict their large-scale industrial application to some extent. With the development of surface engineering technology, laser cladding technology has provided a feasible way to solve this problem by preparing tungsten-based metal coatings on the surface of conventional structural materials. Fusing tungsten-based coatings on the surface of traditional structural components can not only significantly reduce the consumption of precious metals and manufacturing costs, but also endow the surface of the components with the high hardness and wear resistance of tungsten, which is conducive to promoting its engineering applications.
[0004] During laser cladding, due to the inherent brittleness of tungsten and the significant difference in thermal expansion coefficients and melting point range between tungsten and the iron-based substrate, the cladding layer is susceptible to rapid heating and cooling, ultra-high temperature gradients, and multiple overlapping thermal cycles, resulting in significant residual thermal stress. When the local tensile stress exceeds the material's fracture limit, the coating is prone to developing through-cracks or even peeling off, making it difficult to prepare a high-performance cladding layer without crack defects. This severely restricts the large-scale industrial application of tungsten-based metal coatings. Summary of the Invention
[0005] This invention addresses the problem of easy cracking of existing tungsten-based metal coatings during laser cladding by providing a crack-free, high-strength, wear-resistant tungsten-based metal coating with in-situ generation of γ-(Fe,Ni) tough phases between dendrites and its preparation method.
[0006] To achieve the above objectives, the present invention adopts the following technical solution:
[0007] In a first aspect, the present invention provides a method for preparing a crack-free, high-strength, wear-resistant tungsten-based metal coating with an in-situ constructed FCC tough phase, comprising the following steps:
[0008] Step 1: Dry the W-Ni alloy powder under vacuum conditions;
[0009] Step 2: The W-Ni alloy powder is fed to the surface of the iron-based substrate to be clad using a coaxial powder feeding method. Under a protective atmosphere, single-layer multi-pass reciprocating laser cladding is performed according to the set laser cladding process parameters. This allows the W-Ni alloy powder and the surface layer of the iron-based substrate to melt synchronously to form a molten pool. The gradient melting of Fe elements in the substrate is controlled by the laser energy density. The Fe elements in the powder and Ni elements in the powder form a continuous network (FCC) γ-(Fe,Ni) tough phase network in situ in the dendritic segregation region, resulting in a tungsten-based metal coating that is metallurgically bonded to the substrate and free of through cracks.
[0010] Preferably, in step 1, the W-Ni alloy powder contains 75%–85% W and 15%–25% Ni by mass percentage, more preferably 80% W and 20% Ni; the purity of the W-Ni alloy powder is greater than 99.9%, the particle size range is 15–100 μm, and the average Feret particle size is 35–50 μm.
[0011] Preferably, in step 1, the temperature of the vacuum drying process is 80–120°C, and the holding time is 1–4 hours.
[0012] Preferably, in step 2, the surface of the iron base to be clad is cleaned. The specific process is as follows: the surface of the iron base to be clad is polished with sandpaper and then cleaned with ethanol and acetone in sequence to remove oxides, oil stains and impurities from the surface to be clad.
[0013] Preferably, the iron-based matrix is AISI 1045 steel; the chemical composition of the iron-based matrix, by mass percentage, includes: C 0.35%–0.50%, Si 0.10%–0.40%, Mn 0.40%–0.80%, Ni ≤ 0.30%, Cr ≤ 0.30%, with the balance being Fe and unavoidable impurities.
[0014] Preferably, in step 2, the laser cladding parameters are: laser power of 1800–2200 W, scanning rate of 350–450 mm / min, powder feeding rate of 14–18 g / min, laser spot diameter of 3.0–4.0 mm, and overlap rate of adjacent cladding channels of 45%–55%; the coaxial powder-carrying gas and protective gas are both high-purity argon. By controlling the laser cladding parameters, the mass percentage of Fe element diluted from the iron-based matrix to the molten pool during the laser cladding process is controlled to be 18%–30%, so that the cladding layer forms an adaptive gradient structure in which the volume fraction of γ-(Fe,Ni) phase first increases and then decreases along the thickness direction from the matrix to the coating surface.
[0015] Preferably, the thickness of the obtained tungsten-based metal coating is 1.5–2.0 mm; the average microhardness of the coating is not less than 550 HV; and the average fracture toughness of the coating is not less than 10 MPa·m. 1 / 2 Under test conditions of 15N normal load, 4mm reciprocating stroke, 4mm / s sliding speed, and 30min, the average friction coefficient of the obtained coating is ≤0.60, and the wear rate is ≤0.80×10⁻⁶. -4 mm 3 ·N -1 ·m -1 Wear quality loss is reduced by more than 60% compared to the substrate.
[0016] Preferably, the overall composition of the coating, by mass percentage, is: W 62.77%, Fe 23.09%, Ni 14.14%; along the coating thickness direction, the volume fractions of the W solid solution phase at the top, middle, and bottom of the coating are 61.8%, 50.4%, and 43.3%, respectively; the volume fractions of the γ-(Fe,Ni) phase are 31.9%, 43.7%, and 34.6%, respectively; the volume fractions of the (Fe,Ni)3W3C phase are 6.3%, 5.9%, and 7.5%, respectively; and the bottom of the coating also contains 14.6% of the W6Fe7 intermetallic compound phase.
[0017] In a second aspect, the present invention provides a crack-free, high-strength, wear-resistant tungsten-based metal coating prepared by the method described in the first aspect. The microstructure of the coating includes a body-centered cubic (BCC) W solid solution distributed in dendritic form, a face-centered cubic (FCC) γ-(Fe,Ni) ductile phase distributed in the interdendritic region of the W solid solution, and a (Fe,Ni)3W3C carbide second phase dispersed in the region adjacent to the γ-(Fe,Ni) phase matrix. The bottom of the coating near the matrix also contains a W6Fe7 intermetallic compound. The γ-(Fe,Ni) ductile phase is distributed in a continuous or discontinuous network between the dendrites of the W solid solution, which is used to accommodate thermal strain and block or deflect cracks through local plastic deformation during solidification and cooling.
[0018] Thirdly, the present invention also provides the use of the crack-free, high-strength, wear-resistant tungsten-based metal coating prepared by the method described in the first aspect or the crack-free, high-strength, wear-resistant tungsten-based metal coating described in the second aspect as a surface strengthening component.
[0019] Preferably, the surface strengthening component is any one of a radiation shielding component, a nuclear target component, a nuclear power structure component, or a high-temperature wear-resistant steel component.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) This invention departs from the traditional approach of suppressing matrix dilution and innovatively utilizes the in-situ metallurgical reaction between the Fe element melted into the molten pool of the iron-based matrix and the Ni element in the pre-placed W-Ni powder. The melted Fe element and the Ni in the powder work synergistically during rapid solidification, constructing a thermodynamically stable face-centered cubic γ-(Fe,Ni) ductile phase in situ between the dendrites of the brittle W solid solution. The innovative use of the plastic deformation tolerance and dislocation storage capacity of the γ-(Fe,Ni) phase releases the concentrated thermal stress, effectively relaxing the residual tensile stress during the solidification and cooling process, and blocking the initiation and propagation of microcracks. Crack initiation and propagation are suppressed at the source, resulting in a high-performance tungsten-based metal coating free of macroscopic and microscopic crack defects.
[0022] (2) The in-situ constructed network γ-(Fe,Ni) toughness of this invention has significant bridging, deflection and termination passivation effects on the relative extended cracks, and the average fracture toughness of the coating reaches 11.08±0.89 MPa·m. 1 / 2 Meanwhile, by combining solid solution strengthening, rapid solidification dislocation strengthening and fine carbide precipitation strengthening, the average microhardness of the coating reaches 606 HV, achieving a balance between high hardness and high toughness.
[0023] (3) Under dry sliding friction and wear conditions, the average friction coefficient of this invention is reduced to 0.57, and the wear rate is reduced to 0.65×10. -4 mm 3 ·N -1 ·m -1 Wear quality loss was reduced by 69.52%, significantly improving the service life of steel components under heavy wear conditions.
[0024] (4) The present invention does not require the substrate to be preheated at ultra-high temperature. A coating with a thickness of 1.5 to 2.0 mm and good metallurgical bonding can be prepared using a conventional coaxial powder feeding laser cladding system. It is suitable for surface strengthening and remanufacturing of steel parts such as nuclear power structural components. Attached Figure Description
[0025] Figure 1 The images show a comparison of the cross-sectional morphology, composition analysis, and macroscopic forming of the tungsten-based metal coating obtained in Example 1 of this invention. (A) is a SEM image of the cross-sectional micromorphology of the W-Ni tungsten-based metal coating in Example 1; (B) is an EDS energy spectrum and elemental content analysis image of the entire cross-section of the tungsten-based metal coating in Example 1; (C) is a macroscopic image of the surface crack morphology of the pure W laser cladding layer without Ni in the comparative example; and (D) is a macroscopic image of the W-Ni coating without through-cracks obtained after adding Ni in Example 1.
[0026] Figure 2The following is a synchrotron radiation X-ray diffraction (S-XRD) phase analysis diagram of the tungsten-based metal coating obtained in Example 1 of the present invention along the thickness direction, wherein: (A) is the synchrotron radiation X-ray diffraction (S-XRD) spectrum of the top, middle and bottom of the coating along the thickness direction; (B) is a bar chart of the volume fraction distribution of each phase in the top, middle and bottom of the coating obtained by Rietveld refinement calculation; (C) is a local magnified comparison diagram of the main diffraction peaks in the top, middle and bottom of the coating; (D) is a Rietveld refinement fitting and phase calibration curve of the S-XRD diffraction data of the bottom of the coating.
[0027] Figure 3 The images show the microhardness, microcrack resistance mechanism, and dislocation strengthening TEM morphology of the tungsten-based metal coating obtained in Example 1 of this invention, wherein: (A) is a microhardness distribution curve of the coating surface along the depth direction of the cross section to the substrate; (B) is a microcrack resistance mechanism morphology diagram showing the deflection, bridging, and termination passivation of cracks in the γ-(Fe,Ni) toughness under large load indentation; (C) is a transmission electron microscope (TEM) morphology diagram of entangled dislocations inside the face-centered cubic γ-(Fe,Ni) phase; and (D) is a transmission electron microscope (TEM) morphology diagram of the second phase of (Fe,Ni)3W3C carbide hindering dislocation movement and generating dislocation pile-up. Detailed Implementation
[0028] The present invention will be described in detail below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention. The examples given below are not intended to limit the present invention. Unless otherwise specified, all chemical components used in the present invention are by weight percentage.
[0029] Example 1
[0030] A crack-free, high-strength, wear-resistant tungsten-based metal coating with an in-situ constructed FCC tough phase is described. The substrate to be clad is AISI 1045 steel, and the cladding powder is spherical W-Ni alloy powder with a composition of 80% W and 20% Ni. The preparation steps are as follows:
[0031] Step 1: Select an AISI 1045 steel plate with dimensions of 100mm × 100mm × 10mm as the cladding substrate. Its chemical composition is: C 0.43%, Si 0.21%, Mn 0.64%, Ni 0.18%, Cr 0.15%, with the balance being Fe. Mechanically polish the surface of the substrate to be clad with sandpaper to remove the surface oxide scale. Then, ultrasonically clean it in alcohol and acetone solvents in sequence to remove oil and impurities adhering to the surface.
[0032] Step 2: Select spherical W-Ni alloy powder with a purity greater than 99.9% and an average Feret particle size of 43.3 μm as the cladding material. Place the W-Ni alloy powder to be clad in a vacuum drying oven and vacuum dry it at 100℃ for 2 hours to completely remove the adsorbed moisture and enhance its flowability.
[0033] Step 3: Load the dried W-Ni alloy powder into the coaxial powder feeder of the laser cladding system. Laser cladding is performed using an LDM1500-5N high-power fiber laser integrated into a KUKA six-axis robot. The cladding process parameters are set as follows: laser power 2000W, scanning speed 400mm / min, powder feed rate 16g / min, laser circular spot diameter 3.5mm, and overlap rate of adjacent cladding passes 50%. High-purity argon gas is used as the powder carrier gas and protective atmosphere for the molten pool throughout the cladding process, and the nozzle scans along a pre-defined single-layer, multi-pass strip reciprocating path.
[0034] Step 4: After laser cladding, the sample is naturally cooled to room temperature under argon protection. During the cladding process, the substrate surface undergoes slight melting, and Fe element is stably diluted and enters the molten pool, rapidly dissolving and solidifying with the W-Ni alloy. The resulting coating thickness is approximately 1.8 mm, with a dense and uniform cross-sectional structure. Figure 1 As shown in (A) in the figure. The results were obtained from EDS energy dispersive spectroscopy measurements across the entire region, as shown in (A). Figure 1 In (B), the overall average composition of the coating is 62.77% W, 23.09% Fe, and 14.14% Ni. Figure 1 In contrast to (C), the surface of the pure W laser cladding layer without Ni has a large number of through cracks; while the W-Ni coating prepared by adding Ni in this invention has a smooth and uniform surface. Figure 1 (D) shows multiple overlapping cracks without penetrating cracks.
[0035] Characterization and testing:
[0036] (1) Characterization of phase composition and microstructure
[0037] Phase composition and microstructure characterization analysis were performed on the crack-free tungsten-based metal coating prepared in Example 1: The sample obtained in Example 1 was cut into a cross-section perpendicular to the scanning direction. After stepwise grinding and polishing, high-energy synchrotron X-ray diffraction (S-XRD) tests were conducted at the BL12SW beamline of the Shanghai Synchrotron Radiation Facility (SSRF). The X-ray wavelength was 0.1256 Å, the energy was 160 keV, and the spot size was 500 μm × 500 μm. Diffraction patterns were collected along the coating thickness direction at the top, middle, and bottom. The results are as follows: Figure 2 As shown in (A) in the figure. The test results are compared with the local magnified view of the main diffraction peaks. Figure 2The (C) and Rietveld full-spectrum refinement show that the top and middle parts of the coating consist of a body-centered cubic (BCC)W solid solution phase, a face-centered cubic (FCC) γ-(Fe,Ni) phase, and a small amount of Fd-3m structured (Fe,Ni)3W3C intermetallic carbide phase; the bottom region of the coating, in addition to the above three phases, also contains a small amount of R-3m structured W6Fe7 intermetallic compound phase. Rietveld full-spectrum refinement was used to fit and analyze the S-XRD diffraction data of the bottom of the coating, as shown in the figure. Figure 2 As shown in (D), the fine-fit fitting factor Rw is 9.617, and the diffraction peaks of each phase show good agreement.
[0038] The phase volume fraction at different depths of the coating section was quantitatively calculated using Rietveld refinement, such as... Figure 2 As shown in (B): the W solid solution phase contents at the top, middle, and bottom of the coating are 61.8%, 50.4%, and 43.3%, respectively; the γ-(Fe,Ni) toughening phase contents are 31.9%, 43.7%, and 34.6%, respectively; the (Fe,Ni)3W3C carbide contents are 6.3%, 5.9%, and 7.5%, respectively; and the W6Fe7 phase content at the bottom is 14.6%. The measured lattice constants of the BCC phase W solid solution at the top, middle, and bottom of the coating are 3.174 Å, 3.167 Å, and 3.166 Å, respectively.
[0039] (2) Mechanical properties and wear resistance / friction reduction performance tests were conducted on the tungsten-based metal coating and AISI1045 steel substrate prepared in Example 1:
[0040] Microhardness testing: An HVS-1000A Vickers microhardness tester was used. A load of 300g was applied, and the holding time was 10s. Ten points were tested at regular intervals along the coating surface to the substrate cross-section, and the average value was taken. The test curve is shown below. Figure 3 As shown in (A), the microhardness of the obtained tungsten-based metal coating is stable at about 600 HV (average hardness reaches 606 HV), which is about 2.4 times the hardness of AISI 1045 steel substrate (about 250 HV); the hardness transitions smoothly in a stepwise manner from the heat-affected zone (HAZ) to the substrate; the hardness at the bottom of the coating shows a slight upward trend due to the precipitation of high-hardness W6Fe7 intermetallic phase.
[0041] Characterization of fracture toughness and crack resistance mechanism: Microcracks were induced by applying a 5 N indentation load to a microhardness tester. Figure 3 As shown in (B), the microcracks initiated by the indentation propagate within the brittle BCC phase W solid solution, but exhibit significant crack deflection, bridging, and termination passivation upon encountering the FCC structure γ-(Fe,Ni) ductile phase. Based on Laugier's indentation fracture toughness formula, the average fracture toughness of the coating reaches 11.08 ± 0.89 MPa·m. 1 / 2The room temperature elastic modulus E of the coating, as measured by micro tensile testing, is approximately 279 GPa.
[0042] Friction and wear performance testing: The MPX-2000A ball-disc reciprocating friction and wear testing machine was used. Testing was conducted under dry friction conditions at room temperature. The wear pair consisted of SiC ceramic balls. The normal load was 15 N, the unidirectional reciprocating stroke was 4 mm, the sliding speed was 4 mm / s, and the test lasted for 30 min. Test results showed that the wear tracks on the AISI1045 steel substrate were wide and deep (maximum wear depth approximately 4.5 μm), with severe plastic deformation, deep furrows, and large pieces of flaking debris on the worn surface. In contrast, the wear tracks on the tungsten-based metal coating were significantly shallower and narrower (maximum depth only approximately 1.5 μm). The average coefficient of friction of the coating was only 0.57, a 17.39% reduction compared to the AISI1045 steel substrate (0.69); the wear rate of the coating was 0.65 × 10⁻⁶. -4 mm 3 ·N -1 ·m -1 Compared to the matrix (1.13×10 -4 mm 3 ·N -1 ·m -1 The wear mass was reduced by 42.48%; the wear mass loss was only 3.2mg, which was 69.52% lower than that of the matrix (10.5mg), demonstrating excellent high strength and wear resistance.
[0043] (3) Quantitative Verification and Microscopic Analysis of Crack Resistance Energy Absorption Mechanism and Multiple Strengthening Mechanism: The crack resistance energy absorption mechanism and multiple strengthening mechanism of the FCC tough phase in the coating obtained in Example 1 were quantitatively verified and microscopically analyzed: The local orientation difference (KAM) and geometrically necessary dislocation (GND) density distribution of the coating cross section were analyzed using EBSD technology. The test analysis showed that the local strain was mainly concentrated in the γ-(Fe,Ni) phase region between dendrites, and the average GND dislocation density of the γ-(Fe,Ni) tough phase was as high as 12.239 × 10⁻⁶. 14 m -2 It is significantly higher than the 4.941 × 10⁻⁶ of BCC W solid solution. 14 m -2 This demonstrates that the face-centered cubic γ-(Fe,Ni) phase possesses extremely high dislocation storage and local plastic deformation tolerance capabilities. During rapid solidification, it effectively absorbs the thermal strain generated by the interphase thermal expansion mismatch through plastic deformation, thereby completely eliminating the through-crack initiation.
[0044] Transmission electron microscopy (TEM) was used to further observe the internal microstructure and strengthening mechanism of the coating: (1) Solid solution strengthening: Rapid laser cooling caused Fe and Ni to dissolve into the W lattice, and W to dissolve into the γ-(Fe,Ni) lattice. The lattice distortion rates of the W solid solution and the γ-(Fe,Ni) phase were calculated to be 2.62% and 3.47%, respectively, forming significant solid solution strengthening; (2) Dislocation strengthening: such as Figure 3 As shown in (C), ultrafast solidification introduces high-density entangled dislocations into the face-centered cubic γ-(Fe,Ni) phase, which significantly improves the deformation resistance of the tough phase itself; (3) Second phase strengthening: as shown in (C) Figure 3 As shown in (D), the submicron (Fe,Ni)3W3C carbides dispersed on the matrix cannot be cut by dislocations, resulting in significant dislocation pile-up and bypass strengthening (Orowan mechanism). The synergistic effect of these multiple mechanisms enables the tungsten-based coating with the introduction of the FCC toughening phase to maintain an ultra-high hardness of over 600 HV while achieving excellent crack resistance and toughening.
[0045] Comparative Example 1
[0046] The Scheil-Gulliver nonequilibrium solidification model was used to simulate the solidification path of a W-Fe binary system without Ni. The composition was set to 76.91% W and 23.09% Fe, corresponding to the cladding pool state of pure W powder at the same Fe dilution rate.
[0047] Calculation results show that the system first precipitates a BCC solid solution phase at 2646℃, and then precipitates trace amounts of Fe7W6 when the temperature drops to approximately 1648℃. However, the final room-temperature solidification structure consists entirely of brittle BCC and intermetallic compound phases, failing to form the strain-accommodating FCC structure γ-(Fe,Ni) tough phase in situ. This comparative example conversely demonstrates that the synergistic reaction between the introduction of Ni into the cladding material and the dilution of Fe in the matrix is an irreplaceable key technical feature for constructing the FCC tough phase in situ during solidification to eliminate cracking in the cladding layer.
[0048] In summary, this invention optimizes and controls the metallurgical reaction between W-Ni alloy powder and diluted Fe elements in the matrix, thereby constructing a network-distributed FCC structure γ-(Fe,Ni) tough phase in situ during laser rapid solidification. This results in a high-performance tungsten-based metal coating with excellent interfacial bonding with the matrix, no crack defects, and both high hardness and ultra-high wear resistance.
Claims
1. A method for preparing a crack-free, high-strength, wear-resistant tungsten-based metal coating, characterized in that, Includes the following steps: Step 1: Dry the W-Ni alloy powder under vacuum conditions; Step 2: The W-Ni alloy powder is fed to the surface of the iron-based substrate to be clad using a coaxial powder feeder. Under a protective atmosphere, single-layer multi-pass reciprocating lap laser cladding is performed according to the set laser cladding process parameters to obtain a tungsten-based metal coating that is metallurgically bonded to the substrate and has no through cracks.
2. The preparation method according to claim 1, characterized in that, The W-Ni alloy powder comprises, by mass percentage, 75%–85% W and 15%–25% Ni, preferably 80% W and 20% Ni; and / or, the purity of the W-Ni alloy powder is greater than 99.9%; and / or, the particle size range is 15–100 μm; and / or, the average Feret particle size is 35–50 μm.
3. The preparation method according to claim 1, characterized in that, The vacuum drying process is carried out at a temperature of 80–120°C and / or for a holding time of 1–4 hours.
4. The preparation method according to claim 1, characterized in that, The surface of the iron-based substrate to be clad is to be cleaned. The specific process is as follows: the surface of the iron-based substrate to be clad is polished with sandpaper, and then cleaned with ethanol and acetone in sequence to remove oxides, oil stains and impurities from the surface to be clad.
5. The preparation method according to claim 1, characterized in that, The iron-based matrix is AISI 1045 steel; and / or, the iron-based matrix comprises, by mass percentage: C 0.35%–0.50%, Si 0.10%–0.40%, Mn 0.40%–0.80%, Ni ≤ 0.30%, Cr ≤ 0.30%, with the balance being Fe and unavoidable impurities.
6. The preparation method according to claim 1, characterized in that, The laser cladding parameters are as follows: laser power of 1800-2200 W, scanning rate of 350-450 mm / min, powder feeding rate of 14-18 g / min, laser spot diameter of 3.0-4.0 mm, and overlap rate of adjacent cladding channels of 45%-55%; the coaxial powder feeding carrier gas and protective gas are both high-purity argon.
7. A crack-free, high-strength, wear-resistant tungsten-based metal coating prepared by the method according to any one of claims 1-6, characterized in that, The microstructure of the tungsten-based metal coating includes a body-centered cubic W solid solution distributed in dendritic form, a face-centered cubic γ-(Fe,Ni) ductile phase distributed in the interdendritic region of the W solid solution, and a (Fe,Ni)3W3C carbide second phase dispersed in the region adjacent to the γ-(Fe,Ni) phase matrix; the bottom of the coating near the matrix also contains W6Fe7 intermetallic compounds; the γ-(Fe,Ni) ductile phase is distributed in a continuous or discontinuous network between the dendrites of the W solid solution, which is used to accommodate thermal strain and block or deflect cracks through local plastic deformation during solidification and cooling.
8. The crack-free, high-strength, wear-resistant tungsten-based metal coating as described in claim 7, characterized in that, The tungsten-based metal coating has a thickness of 1.5–2.0 mm; and / or, the average microhardness of the tungsten-based metal coating is not less than 550 HV; and / or, the average fracture toughness of the tungsten-based metal coating is not less than 10 MPa·m. 1 / 2 And / or, under test conditions of 15N normal load, 4mm reciprocating stroke, 4mm / s sliding speed and 30min, the average coefficient of friction of the tungsten-based metal coating is ≤0.60, and the wear rate is ≤0.80×10⁻⁶. -4 mm 3 ·N -1 ·m -1 Wear quality loss is reduced by more than 60% compared to the substrate.
9. The crack-free, high-strength, wear-resistant tungsten-based metal coating as described in claim 7, characterized in that, The overall composition of the tungsten-based metal coating, by mass percentage, is: W 62.77%, Fe 23.09%, and Ni 14.14%. Along the coating thickness direction, the volume fractions of the W solid solution phase at the top, middle, and bottom of the coating are 61.8%, 50.4%, and 43.3%, respectively; the volume fractions of the γ-(Fe,Ni) phase are 31.9%, 43.7%, and 34.6%, respectively; the volume fractions of the (Fe,Ni)3W3C phase are 6.3%, 5.9%, and 7.5%, respectively; and the bottom of the coating also contains 14.6% of the W6Fe7 intermetallic compound phase.
10. Use of the crack-free, high-strength, wear-resistant tungsten-based metal coating prepared by the method of any one of claims 1-6 or the crack-free, high-strength, wear-resistant tungsten-based metal coating as described in any one of claims 7-9 as a surface-strengthening component.
